Stress assignment in polysyllabic words in Levantine Arabic: An Optimality-Theoretic analysis - Guba, Mohammed Nour Abu (Lingua Posnaniensis, 2018)
This paper proposes an Optimality-Theoretic analysis of stress assignment in Levantine Arabic. The proposed hierarchy incorporates two constraints, namely *EXTENDED-LAPSE-R, which restricts stress to one of the last three syllables, and ALIGN-LEFT, which demands that the left edge of the prosodic word be aligned with a foot. This hierarchy is superior to earlier research as it successfully accounts for stress assignment in a more comprehensive and economical way. Most interestingly, it can account for the unexpected stress on a light penult in prosodic words ending in four light syllables and the paradoxical status of foot extrametricality without ad hoc parameterization of constraints. Moreover, findings show that footing in Levantine Arabic is iterative, an indication that secondary stress is attested in Levantine dialects.